An Early Neogene—Early Quaternary Contourite Drift System on the SW Barents Sea Continental Margin, Norwegian Arctic - Rydningen, Tom Arne; Høgseth, Gert; Lasabuda, Amando Putra Ersaid; Laberg, Jan Sverre; Safronova, Polina; Forwick, Matthias (Geochemistry, Geophysics, Geosystems, 2020)
The onset and evolution of the middle to late Cenozoic “icehouse” world was influenced by the development of the global ocean circulation linking the Norwegian–Greenland Sea-Arctic Ocean to the Atlantic Ocean. The evolution of the early Neogene to early Quaternary Bjørnøyrenna Drift, located at the SW Barents Sea continental margin, shed new light on this important hydrological event. By analyzing seismic data and exploration wellbores, it is found that the drift likely started to form in the early/middle Miocene, probably as a result of an ocean circulation reorganization following the opening of the Fram Strait gateway (c. 17 Ma) and subsidence of the Greenland–Scotland Ridge (c. 12 Ma). Thus, the onset of drift growth is considered to have happened close in time to the Mid Miocene Climatic Optimum at 16–14 Ma, and was part of a regional onset of large-scale ocean circulation in the Norwegian–Greenland Sea that influenced the subsequent climate cooling. The drift continued to grow under the influence of early Quaternary glacimarine sedimentation, and later overtopping of the drift mound by downslope transfer of glacigenic sediments during full-glacial conditions resulted in a submarine failure. For the first time, minimum average sedimentation rates of a Neogene to Quaternary drift in this area is calculated, giving rates of 0.020–0.031 m/Kyr. These values are comparable to average deep-sea sedimentation rates from modern low-latitude river systems such as the Amazon and Mississippi, but lower than the Quaternary glacial sedimentation rates from the Barents Sea and Fennoscandian continental margins